Influence of a phyA Mutation on Polyamine Metabolism in Arabidopsis Depends on Light Spectral Conditions - Rahman, Altafur; Tajti, Judit; Majláth, Imre; Janda, Tibor; Prerostova, Sylva; Ahres, Mohamed; Pál, Magda (Plants (Basel, Switzerland), 2023)
The aim of the study was to reveal the influence of phyA mutations on polyamine metabolism in Arabidopsis under different spectral compositions. Polyamine metabolism was also provoked with exogenous spermine. The polyamine metabolism-related gene expression of the wild type and phyA plants responded similarly under white and far-red light conditions but not at blue light. Blue light influences rather the synthesis side, while far red had more pronounced effects on the catabolism and back-conversion of the polyamines. The observed changes under elevated far-red light were less dependent on PhyA than the blue light responses. The polyamine contents were similar under all light conditions in the two genotypes without spermine application, suggesting that a stable polyamine pool is important for normal plant growth conditions even under different spectral conditions. However, after spermine treatment, the blue regime had more similar effects on synthesis/catabolism and back-conversion to the white light than the far-red light conditions. The additive effects of differences observed on the synthesis, back-conversion and catabolism side of metabolism may be responsible for the similar putrescine content pattern under all light conditions, even in the presence of an excess of spermine. Our results demonstrated that both light spectrum and phyA mutation influence polyamine metabolism.
Keywords: phytochrome; far-red light; spermine; blue light